Open Access Musicology Volume One - Barolsky, Daniel; Epstein, Louis (Lever Press, 2020)
"In the fall of 2015, a collection of faculty at liberal arts colleges began a conversation about the challenges we faced as instructors: Why were there so few course materials accessible to undergraduates and lay readers that reflected current scholarly debate? How can we convey the relevance of studying music history to current and future generations of students? And how might we represent and reflect the myriad, often conflicting perspectives, positions, and identities that make up both music's history and the writers of history? Here we offer one response to those questions. Open Access Musicology is a collection of essays, written in an accessible style and with a focus on modes of inquiry rather than content coverage. Our authors draw from their experience as scholars but also as teachers. They have been asked to describe why they became musicologists in the first place and how their individual paths led to the topics they explore and the questions they pose. Like most scholarly literature, the essays have all been reviewed by experts in the field. Unlike all scholarly literature, the essays have also been reviewed by students at a variety of institutions for clarity and relevance. These essays are intended for undergraduates, graduate students, and interested readers without any particular expertise. They can be incorporated into courses on a range of topics as standalone readings or used to supplement textbooks. The topics introduce and explore a variety of subjects, practices, and methods but, above all, seek to stimulate classroom discussion on music history's relevance to performers, listeners, and citizens."